Management and Control of a Fuel Cell, Solar Photovoltaic, and Battery Energy Storage System Linked to a DC Nano Grid - Mounica Patil; Muniraj R.; Sethi Gaurav; Anusuya Devi V.S.; Priyan Shanmuga; Mahesh M. (E3S Web of Conferences)
The electric grid can be connected to non-conventional energy sources such as solar cells and fuel cells to effectively meet the distribution- side load requirements. The electricity grid has started incorporating more battery-powered energy storage systems (BESS), which increases the demand for energy management systems. In this study, we looked at various different PV operating modes, as well as an FC-based DC Nano Grid that was powered by BESS, and a recommendation towards an efficient energy management system are all explored. The primary benefit is that it maintains a consistent direct current (DC) voltage across the grid. The Simulink/MATLAB software is used extensively in these simulated case studies.